Predictors of time to complete toileting for children with spina bifida. Issue 5 (16th June 2013) - Gribble, Nigel; Parsons, Richard; Donlau, Marie; Falkmer, Torbjorn
<x xml:space="preserve">Abstract</x> Background/aim Previous research has shown that children with spina bifida use clean intermittent catheterisation for urination, a rather complex procedure that increases the time taken to completion. However, no studies have analysed the factors impacting on the time taken to complete the urination that could inform occupational therapy practice. Therefore, the aim was to identify the variables that predict extended time children with spina bifida take to complete urination. Methods Fifty children, aged 5–18 years old with spina bifida using clean intermittent catheterisation, were observed while toileting and responding to a set of assessments tools, among them the Canadian Occupational Performance Measure. A logistic regression was used to identify which variables were independently associated with an extended toileting time. Results Children with spina bifida do take long time to urinate. More than half of this study's participants required more than five minutes completing urination, but not all required extended times. Ambulant, independent girls were more likely to perform toileting in less than six minutes compared with other children with spina bifida. However, age, IQ, maintained focus on the task, Canadian Occupational Performance Measure, time processing abilities and self‐reported ratings of independence appeared to be of no relevance, to predict extended toileting times. Conclusion To minimise occupational disruption caused by extended toileting times, occupational therapists should utilise the relevant predictors: gender, independence and ambulation when they prioritise children for relevant interventions.